CSE390D Notes for Friday, 10/18/24

turning to induction, chapter 5 Trying to prove some P(n) for n in some set of integers that has a least one element. Two step process: 1) Prove P(min) where min is least 2) Prove that P(k) -> P(k + 1) whenever k in set ladder analogy recursion analogy There is a certain template that I want to follow for these proofs. Best to follow some examples. ------------------------------------------------------------------------------- Show that: 1 + 2^1 + 2^2 + ... + 2^n = 2^(n+1) - 1 We prove using induction P(n): sum(i = 0 to n of 2^i) = 2^n-1 for n in N Prove P(0): 1 = 2 - 1 = 2^1 - 1 = 2^(0+1) - 1 Prove that P(k) -> P(k+1) for k in N P(k): sum(i=0 to k of 2^i) = 2^(k + 1) - 1 P(k+1): sum(i=0 to k+1 of 2^i) = 2^(k+2) - 1 Assume P(k) is true for some k in N sum(i=0 to k+1 of 2^i) = sum(i=0 to k of 2^i) + 2^(k+1) using inductive hypothesis: = 2^(k+1) - 1 + 2^(k+1) = 2 * 2^(k+1) - 1 = 2^(k+2) - 1 QED ------------------------------------------------------------------------------- Why does it work? proof by contradiction well-ordering principle ------------------------------------------------------------------------------- Show that 2^n < n! for n in {x | x in an integer >= 4} P(4): 2^4 = 16 < 24 = 4! Prove that P(k) -> P(k+1) for k in N P(k): 2^k < k! P(k+1): 2^(k+1) < (k+1)! Assume P(k) is true for some k in N 2^(k+1) = 2 * 2^k using inductive hypothesis: < 2 * k! < (k+1) * k! (because k+1 > 2) = (k+1)! QED ------------------------------------------------------------------------------- Show that: 3 | (n^3 - n) for all nonnegative n We prove using induction P(n): 3 | (n^3 - n) for n in N Prove P(0): 0^3 - 0 = 0 = 0 * 3 Prove that P(k) -> P(k+1) for k in N P(k): 3 | (n^3 - n) n^3 - n = 3a (for some a) P(k+1): 3 | (n+1)^3 - (n + 1) (n+1)^3 - (n + 1) = 3b (for some b) Assume P(k) is true for some k in N (n+1)^3 - (n + 1) = (n^3 + 3n^2 + 3n + 1) - (n + 1) = (n^3 + 3n^2 + 3n) - n = (n^3 - n) + 3(n^2 + n2) using inductive hypothesis, exists a such that n^3 - n = 3a (n+1)^3 - (n+1) = n^3 - n + 3(n^2 + n) = 3a + 3(n^2+n) = 3(a + n^2 + n) (algebra) So 3 | ((n+1)^3 - (n+1)) QED ------------------------------------------------------------------------------- Show that: 1^2 + 2^2 + 3^2 + ... + n^2 = n(n+1)(2n+1)/6 We prove using induction P(n): sum(i = 1 to n of i^2) = n(n+1)(2n+1)/6 for n in Z+ Prove P(1): 1^2 = 1 = 6/6 = 1*2*3/6 = 1*(1+1)(2*1+1)/6 Prove that P(k) -> P(k+1) for k in N P(k): sum(i = 1 to k of i^2) = k(k+1)(2k+1)/6 P(k+1): sum(i = 1 to k+1 of i^2) = (k+1)(k + 2)(2(k+1) + 1)/6 Assume P(k) is true for some k in N sum(i = 1 to k+1 of i^2) = sum(i = 1 to k of i^2) + (k+1)^2 using inductive hypothesis: = k(k+1)(2k+1)/6 + (k+1)^2 = (k+1)(k(2k+1)/6 + k + 1) = (k+1)(k(2k+1)/6 + 6(k+1)/6) = (k+1)(k(2k+1) + 6(k+1))/6 = (k+1)(2k^2 + k + 6k + 6)/6 = (k+1)(2k^2 + 7k + 6)/6 = (k+1)(k + 2)(2k + 3)/6 = (k+1)(k + 2)(2(k+1) + 1)/6 QED
Stuart Reges
Last modified: Fri Oct 18 13:07:18 PDT 2024